A Study on Proline and Glycine Betaine Contents as Salinity and Drought Tolerant Indicators in Capsicum Annuum L. (Cultivar: Roma). (Global Journal of Science Frontier Research, 2018)
In this research, accumulation of free proline and Glycine betaine contents was investigated in Solanum lycopersicum L. in response to environmental stress (drought and salinity). After salt and drought treatments in the field the plant samples both stressed and unstressed were used to evaluate the level of free proline and Glycine betaine contents. Proline and Glycine betaine content increase significantly (P
Keywords: proline; glycine betaine; solanum lycopersicum; drought; salinity